Futech.Edu (Future Technology Education): teaching and learning application design in the society 5.0 / Era Yaka Samudra Pati … [et al.] - Yaka Samudra Pati, Era; Ainanur, Ainanur; Al Mahfira, Al Mahfira; Amanda Putri, Alya Aqilah; Fadjryani, Fadjryani (Faculty of Computer and Mathematical Sciences, 2023)
Education is a critical issue in Indonesia. Central Sulawesi is one of the regions with the lowest quality of education in Indonesia, but has the potential to become an advanced and developing region in the field of education, which is due to several things such as large human resource potential. The Ministry of Education, Culture, Research, and Technology (KEMENDIKBUDRISTEK) has launched "Kurikulum Merdeka" in 2022 to address educational challenges. However, its implementation faces obstacles due to low literacy levels, complicated education administration and the lack of implementation of education digitalization. Futech.Edu, also known as Future Technology Education, is a digital education application in the era of Society 5.0 with three main functions, namely Teacher's Classroom, Student's Dashboard and Parent's Monitoring, which combines rarely found educational features into one application. These features include E-Raport to improve the efficiency of recapping student grades every semester at the elementary, middle, high school education levels, providing a teaching and learning system with three learning strategy options, namely inquiry based learning, problem based learning or project based learning so that teachers can create efficient and interactive classes, providing interest, talent, literacy and numeracy tests, national competition information for students, that are rarely updated on other platforms, providing an academic monitoring system and the development of children's potential for parents without logging into their child's account. The implementation of Futech.Edu has the potential to accelerate regional progress, especially in Central Sulawesi, which will ultimately contribute to national development for the long-term quality of education in Indonesia.